Dynamic Inducements in R&D Investment: Market Signals and Network Locations - Soh, Pek-Hooi; Mahmood, Ishtiaq Pasha; Mitchell, Will (Academy of Management Journal, 2004)
This research shows that alliance networks shape how firms respond to uncertainty-reducing information generated outside a network. Product awards signal the potential commercial success of the award-winning firms, which reduces the uncertainty of new R&D investment. Networks magnify or diminish a firm's R&D response to the market signals, depending on the firm's network location, partners' success, technical proximity to partners, and relative capabilities. The study examined 198 U.S. computer and telecommunications firms from 1991 to 2000.